The safety of paediatric surgery between COVID‐19 surges: an observational study. (13th October 2020) - Okonkwo, I. N. C.; Howie, A.; Parry, C.; Shelton, C. L.; Cobley, S.; Craig, R.; Permall, N.; El‐Sheikha, S. H.; Herbert, N.; Arnold, P.
Summary: Despite the ongoing coronavirus disease 2019 (COVID‐19) pandemic, elective paediatric surgery must continue safely through the first, second and subsequent waves of disease. This study presents outcome data from a children's hospital in north‐west England, the region with the highest prevalence of COVID‐19 in England. Children and young people undergoing elective surgery isolated within their household for 14 days, then presented for real‐time reverse transcriptase polymerase chain reaction testing for severe acute respiratory syndrome coronavirus disease‐2 (SARS‐CoV‐2) within 72 h of their procedure (or rapid testing within 24 h in high‐risk cases), and completed a screening questionnaire on admission. Planned surgery resumed on 26 May 2020; in the four subsequent weeks, there were 197 patients for emergency and 501 for elective procedures. A total of 488 out of 501 (97.4%) elective admissions proceeded, representing a 2.6% COVID‐19‐related cancellation rate. There was no difference in the incidence of SARS‐CoV‐2 among children and young people who had or had not isolated for 14 days (p > 0.99). One out of 685 (0.1%) children who had surgery re‐presented to the hospital with symptoms potentially consistent with SARS‐CoV‐2 within 14 days of surgery. Outcomes were similar to those in the same time period in 2019 for length of stay (p = 1.0); unplanned critical care admissions (p = 0.59); and 14‐day hospital re‐admission (p = 0.17). However, the current cohort were younger (p = 0.037); of increased complexity (p < 0.001) and underwent more complex surgery (p < 0.001). The combined use of household self‐isolation, testing and screening questionnaires has allowed the re‐initiation of elective paediatric surgery at high volume while maintaining pre‐COVID‐19 outcomes in children and young people undergoing surgery. This may provide a model for addressing the ongoing challenges posed by COVID‐19, as well as future pandemics.